2012
DOI: 10.1021/ic201654d
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Compatible, Phosphorescent Dimetallic Rhenium Complexes Linked through Functionalized Alkyl Chains: Syntheses, Spectroscopic Properties, and Applications in Imaging Microscopy

Abstract: A range of luminescent, dimetallic complexes based upon the rhenium fac-tricarbonyl diimine core, linked by aliphatic chains of varying lengths and functionality, have been synthesized and their photophysical properties examined. Each complex displays characteristic (3)M(Re)L(diimine)CT emission in aerated acetonitrile solution, with long lifetimes in the range of 129-248 ns and corresponding quantum yields in the range 3.2-8.0%. In aqueous solution, as opposed to acetonitrile, the complexes generally show a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Several rhenium polypyridyl‐based molecular probes have been described recently . One is described as a ‘sleeping Trojan horse’ because the complex acts as a vessel that is membrane impermeant when unoccupied but exhibits cellular uptake upon loading with metal ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several rhenium polypyridyl‐based molecular probes have been described recently . One is described as a ‘sleeping Trojan horse’ because the complex acts as a vessel that is membrane impermeant when unoccupied but exhibits cellular uptake upon loading with metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…While our initial studies focused on labelled peptides, subsequent results demonstrated that the SAAC concept is quite versatile and may be adapted to other biomolecules as diverse as biotin, folate, vitamin B 12 , insulin and thymidine . Several non‐SAAC‐band luminescent diimine derivatives of the fac ‐{Re(CO) 3 } + core are also described . In the course of these studies, some unusual photophysical effects have been encountered that will be discussed briefly.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes have found particular application in cell imaging [9,[400][401][402][403][404]. Of the transition metals, ruthenium (Ru) complexes remain the most popular, however increasingly iridium (Ir), rhenium (Re), and occasionally osmium (Os) and platinum (Pt) have been used in cell imaging applications [9,[400][401][402][403][404][405]. The current factor limiting widespread adoption of these types of materials is probably commercial availability, as most of the materials are synthesized in-house.…”
Section: Luminescent Transition Metal Complexesmentioning
confidence: 99%
“…[2830], catalysis [31], light-emitting devices [32,33], CO2 fixation [34], optical switches [35,36], bioprobes [37,38] and imaging [39]. As far as we know, there is a limited number of reports available on rhenium(I) complexes attached to the imine ligands [4042].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%